Properties of expression of protein capside porcine circovirus type 2 in bacterial cells - Titova, Anastasia D.; Kudzin, Kirill V.; Prokulevich, Vladimir A. (Experimental Biology and Biotechnology, 2021)
To improve expression of the porcine circovirus type 2 (PCV2) capsid protein in E. coli cells, the corresponding gene was optimized and two variants of the open reading frame were constructed, which encoded the full-sized and shortened capsid proteins as part of the expression vector. Rare codons were replaced, and in the case of a shortened version of the gene, the region corresponding to the N-terminal domain of the protein was deleted. A comparison was made of the expression level of the studied proteins. It was established that the highest level of expression in bacterial cells is achieved by simultaneously optimizing the codons and removing the initial (N-terminal) 108 base pair (bp) portion of the gene, which contains the nuclear localization signal.
Keywords: porcine circovirus type 2; open reading frame; capsid protein; nuclear localization signal; N-terminal portion of the protein; synonymous codons; codon optimization; heterologous host; gene expression; codon adaptation index